Heterogeneous Convergence - Andrew T. Young; Matthew J. Higgins; Daniel Levy (Economics Letters, 2013)
We use US county-level data to estimate convergence rates for 22 individual states. We find significant heterogeneity. E.g., the California estimate is 19.9% and the New York estimate is 3.3%. Convergence rates are essentially uncorrelated with income levels.
Keywords: O40; O11; O18; O51; R11; H50; H70; 330; Economic Growth; Conditional Convergence; Heterogeneity; U.S. County Level Data